Marshall Stability of Porous Asphalt Mixture Incorporating Kenaf Fiber - Nur Ezreen, Jasni; Khairi Azman, Masri; Putra Jaya, Ramadhansyah; Mohd Mustafa Al Bakri, Abdullah; Rafiza, Abd Razak; Nabiałek, Marcin; Błoch, Katarzyna; Śliwa, Agata (Polish Academy of Sciences, 2022)
Porous asphalt mixture (PA), known as open-graded surfaces over a stone bed underneath, allows water to go through. These factors can affect the porous asphalt mixture adhesive strength. The high amount of course aggregate promotes the structure of air voids have certain impacts on the acoustic properties of porous asphalt. The materials properties are consisting of both aggregate and bitumen tests. This study also details out the aggregates sieve analysis test to develop new aggregate gradation for PA. According to five ASEAN countries’ specifications, the sieve analysis test was done. The countries included are Malaysia, Vietnam, Thailand, Singapore, and Indonesia. The test for the binder includes the softening point, penetration, and ductility. This study also investigates the addition of kenaf fiber in the mixture as an additive. Mechanical performance test for PA using Marshall Stability test to identify the strength and the properties of the conventional PA with the addition of kenaf fiber compared to the new gradation of PA incorporating kenaf fiber. From the results, the addition of 0.3% kenaf modified PA improved the performance of PA in terms of Marshall Stability and volumetric properties.